(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Linguistics expertise is this result belongs to questions solution in doing special knowledge application is required​ an expert conclusion to be given with final , procedural in terms of in order inserted , oral and ( or ) written of speech to expertise about linguistic are studies. This article provides reasonable information about the importance and effectiveness of pictograms in today’s study of their place, importance and meaning, in the process of information sharing and interpretation in people’s lives.